Phosphorus Fractionation in Soil Cultivated with Sugarcane Fertilized by Filter Cake and Phosphate Sources - Caione, Gustavo [UNESP]; de Mello Prado, Renato [UNESP]; Campos, Cid Naudi Silva [UNESP]; Rodrigues, Marcos; Pavinato, Paulo Sérgio; Agostinho, Flávia Bastos (Taylor & Francis, 2015)
Studies of phosphorus (P) forms in high-weathering soils, after long periods of phosphate fertilizer application associated with organic residues, are important to optimize P fertilization. This study aims to evaluate the effect of filter cake application and other distinct phosphate sources on organic and inorganic P fractions in Red Eutrophic Argisoil cultivated with sugarcane. The experiment was established between 2012 and 2014, in Sao Paulo State, Brazil. The treatments were as follows: control (without P), triple superphosphate, natural phosphate from Araxá, and naturally reactive phosphate Bayóvar on the presence and absence of filter cake at 7.5 t ha−1 (dry mass). The P rate was 90 kg ha−1 of phosphorus pentoxide (P2O5) soluble in citric acid. The experiment was arranged in a randomized block, in a 4 × 2 factorial with three repetitions. After 22 months of treatments, soil samples were collected on sugarcane planting lines and P fractionation was analyzed. The greatest percentage of P is found as nonlabile P fractions, regardless of filter cake application or not. The use of low solubility sources, such as natural phosphate from Araxá, in association with filter cake has promoted greater solubility of P bound to calcium (Ca), which can enhance the crop uses. Filter cake increases most of labile and moderately labile inorganic P forms in the soil (resin; sodium bicarbonate, NaHCO3; and sodium hydroxide, NaOH, 0.1 mol L−1), which characterizes the importance of this source to sugarcane nutrient supply.
Keywords: Organic residue; phosphorus forms; phosphorus sources; residual effect